Metamorphoses of the Lithuanian Environmental Thought: From the Onset through Enlightenment to Romanticism - Davidavičius, Mantas Antanas (Tautosakos darbai, 2023)
This article treats the Enlightenment and Romanticism as ways of understanding the world (rather than chronologically defined intellectual movements). The article discusses the main philosophical attributes of these worldviews. It demonstrates how shifts from the symbolical reasoning to the Enlightenment, as well as from the Enlightenment to the Romanticism, transformed the Lithuanians’ relations to the natural surroundings. The article also underscores close connections between literature, philosophy and the Lithuanian environmental practices (i. e. environmental laws, and institutions of environmental protection). For this purpose literary examples (such as works by M. Hussovianus, H. D. Thoreau and P. Mérimée), as well as a tale about a boy raised by the bears in Lithuanian woods, are examined in the light of philosophical tendencies and political transformations. The article shows that the Enlightenment, a project based on rationalization and secularization of the world (an attempt to eliminate symbolical reasoning) brought with itself a view of nature as a resource, and a plan to reconstruct nature alonside the industrial model. The environmental protection of the Enlightenment was a science of optimizing the exploitation. The article shows that Romanticism was a rebellion against the Enlightenment, offering a new type of environmental protection: namely, protecting the nature as useful in-itself, and protecting it from the humans.
Keywords: Romanticism; the Enlightenment; symbolical reasoning; conservation of nature; the bear’s child